Haptic Simulators Dentistry Students Clinical Skills in Development: Advantages and Restrictions - Khaytgul, Tuychiboyeva (American Journal of Bioscience and Clinical Integrity, 2025)
Haptic simulators dentistry in education clinical skills develop for innovative tool as wide is being used. This article haptic simulators dentistry students for advantages and restrictions analysis does. Login in part of the subject relevance seeing is issued, methods in the department literature analysis and experimental information based on approaches Results haptic technologies improve motor skills in progress efficiency shows, but discussion in part technician restrictions and cost issues discussion In conclusion, haptic simulators future development and in education place This is emphasized. research dentistry education to improve contribution Addictive.